Χημική απόθεση από ατμό Al, Fe και της προσεγγιστικής διαμεταλλικής φάσης Al13Fe4: Πειράματα και προσομοιώσεις πολλαπλών χωρικών κλιμάκων - Αβιζιώτης, Ιωάννης Γ. (Εθνικό Μετσόβιο Πολυτεχενίο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων, 2016)
Films containing intermetallic compounds exhibit properties and combination of properties which are only partially explored. They carry potential solutions to confer multifunctionality to advanced materials required by industrial sectors and to become a source of breakthrough and innovation. Metalorganic chemical vapor deposition (MOCVD) potentially allows conformal deposition on, and functionalization of complex surfaces, with high throughput and moderate cost. For this reason, it is necessary to control the complex chemical reactions and the transport mechanisms involved in a MOCVD process. In this perspective, computational modeling of the process, fed with experimental information from targeted deposition experiments, provides an integrated tool for the investigation and the understanding of the phenomena occurring at different length scales, from the macro- to the nanoscale. The MOCVD of Al-Fe intermetallic compounds is investigated in the present thesis as a paradigm of implementation of such a combined, experimental and theoretical approach. Processing of the approximant phase Al13Fe4 is particularly targeted, due to its potential interest as low-cost and environmentally benign alternative to noble metal catalysts in the chemical industry. The attainment of the targeted Al13Fe4 intermetallic phase passes through the investigation of the MOCVD of unary Al and Fe films. The MOCVD of Al from dimethylethylamine alane (DMEAA) in the range 139oC-241oC results in pure films. Increase of the deposition temperature yields higher film density and decreased roughness. The Al deposition rate increases to a maximum of 15.5 nm/min at 185oC and then decreases. Macroscopic simulations of the process predict deposition rates in sufficient agreement with experimental measurements, especially in the range 139oC-227oC. At higher temperatures, competitive gas phase and surface phenomena cannot be captured by the applied model. Multiscale modeling of the process predicts the RMS roughness of the films accurately, thus allowing the control of properties such as electrical resistivity which depend on the microstructure. The MOCVD of Fe from iron pentacarbonyl, Fe(CO)5, is investigated in the range 130oC-250oC for the possibility to obtain fairly pure Fe films with low O and C contamination. The surface morphology depends strongly on the temperature and changes are observed above 200oC. The Fe deposition rate increases up to 200oC, to a maximum of 60 nm/min, and then decreases. Moreover, the deposition rate decreases sharply with increasing pressure. Computational predictions capture accurately the experimental behavior and they reveal that the decrease at higher temperatures and pressures is attributed to the high gas phase decomposition rate of the precursor and to inhibition of the surface from CO. The multiscale model calculates RMS roughness in good agreement with experimental data, especially at higher temperatures. Upon investigation of the two processes, a series of Al-Fe co-depositions performed at 200oC results in Al-rich films with a loose microstructure. They contain no intermetallic phases and they are O-contaminated due to the reaction of the Al with the carbonyl ligands. Sequential deposition of Al and Fe followed by in situ annealing at 575oC for 1 h is applied to bypass the O-contamination. The process conditions of Fe are modified to 140oC, 40 Torr and 10 min resulting in O-free films with Al:Fe atomic ratio close to the targeted 13:4 one. Characterization techniques including X-ray diffraction, TEM and STEM/EDX reveal a composition gradient along the thickness of the films, and the formation of the m-Al13Fe4 approximant phase together with secondary Al-Fe intermetallic phases. It is demonstrated that MOCVD is a suitable method to obtain films composed of intermetallic alloys. Such films, conformally processed on complex surfaces can be considered for a variety of applications.